Evaluation of Piper nigrum L. as a prebiotic ingredient using an in vitro colon model - Mohd Nashri, Siti Maisarah (2019)
Piper nigrum L., commonly known as pepper and often referred to as the 'King of Spice', is a well-known spice that is extensively used around the world in fields such as culinary (for its taste and odour) and pharmaceutical (for its complex chemical composition containing alkaloids, flavonoids and polyphenols). However, study on exploring the potential of Piper nigrum L. as a prebiotic is very scarce. Recent studies also show that it has the ability to promote the growth of several· beneficial colonic bacteria especially Bifidobacterium and Lactobacillus. Therefore, the objectives of this study were to evaluate the digestibility of Piper nigrum L. by digestive enzymes of the upper gastrointestinal digestion, determine the selectivity in activity and/or growth of one or finite amount of colon microbiota and analyse metabolites produced from the fermentation of Piper nigrum L. i.e. short chain fatty acids. Two Piper nigrum L. samples; black pepper, grade Special Black Pepper and white pepper, grade Fair Average Quality, were used as test substrates for prebiotic property with inulin being used as the positive control. To identify its digestibility characteristic, in-vitro gastric and duodenal digestion were conducted, and the total carbohydrate and piperine content were determined using phenol sulphuric acid method and ethylene dichloride extraction method respectively. It was found that white pepper has a significantly higher digestibility (6.78% ± 2.27) in comparison to inulin (2.03% ± 0.20) where there are no significant difference shown against black pepper (5.99% ± 2.22). The piperine content of both test substrates remained the same before and after the digestion. Inoculated with faecal slurry, the pepper samples were then further examined in in-vitro colon model by a pH-controlled batch culture system. Samples were withdrawn at 0, 6, 12 and 24 hours and analysed for their bacterial count and SCFA content respectively. Both black and white pepper showed no significant difference in most of the tested bacteria population growth when compared to inulin especially in Bifidobacterium spp., Eubacteriumrectale/ Clostridium, Lactobacillus/ Enterococcus, Atopobium cluster, Feacalibacterium prausnitzii. Black and white pepper were found to accumulate a significantly higher amount of acetate (155.99 mM + 5.61) and (151.90 mM ± 4.04) respectively compared to inulin (133.00 mM ± 5.37). Butyrate concentration in white pepper across fermentation time only showed a significant increase after 24 h, but no significant difference was found in the concentration of butyrate with black pepper and inulin. Although some contradiction was observed which was by having higher propionate production against butyrate, but this study showed that Piper nigrum L. could be a promising and valuable contribution as a local prebiotic.